Kajian Semiotika Roland Barthes pada Poster Unicef - Junisti Tamara (Mahesa Research Center, 2020)
United Nations Children's Fund (UNICEF) is an organization from the United Nations that provides humanitarian assistance and welfare development to children and their mothers in developing countries. Until now, UNICEF has published numerous posters containing appeals and warnings to help fellow human beings who are experiencing difficulties. However, some of the posters are difficult to translate directly. This study aims to determine how best to understand the message conveyed by the UNICEF posters. As well as knowing the denotation, connotation and ideology in UNICEF posters. The method used in this research is descriptive qualitative method. The data analysis used is semiotic analysis based on Roland Barthes' theory, namely the meaning of the signifier, signified to determine the meaning of denotation, connotation and ideology on the UNICEF poster. The overall results in this study explain that by utilizing the semiotic analysis method, posters that look quite confusing can be easily understood. Semiotics presents a sequence of processes so as to deliver a work of art and design as steps that can be explained in a structured manner.